An improved multilevel Monte Carlo method for estimating probability distribution functions in stochastic oil reservoir simulations. Issue 12 (30th December 2016) - Lu, Dan; Zhang, Guannan; Webster, Clayton; Barbier, Charlotte
Abstract: In this work, we develop an improved multilevel Monte Carlo (MLMC) method for estimating cumulative distribution functions (CDFs) of a quantity of interest, coming from numerical approximation of large‐scale stochastic subsurface simulations. Compared with Monte Carlo (MC) methods, that require a significantly large number of high‐fidelity model executions to achieve a prescribed accuracy when computing statistical expectations, MLMC methods were originally proposed to significantly reduce the computational cost with the use of multifidelity approximations. The improved performance of the MLMC methods depends strongly on the decay of the variance of the integrand as the level increases. However, the main challenge in estimating CDFs is that the integrand is a discontinuous indicator function whose variance decays slowly. To address this difficult task, we approximate the integrand using a smoothing function that accelerates the decay of the variance. In addition, we design a novel a posteriori optimization strategy to calibrate the smoothing function, so as to balance the computational gain and the approximation error. The combined proposed techniques are integrated into a very general and practical algorithm that can be applied to a wide range of subsurface problems for high‐dimensional uncertainty quantification, such as a fine‐grid oil reservoir model considered in this effort. The numerical results reveal that with the use of the calibrated smoothing function, the improved MLMC technique significantly reduces the computational complexity compared to the standard MC approach. Finally, we discuss several factors that affect the performance of the MLMC method and provide guidance for effective and efficient usage in practice. Key Points: Develop an improved multilevel Monte Carlo method Apply the method to an oil reservoir model Evaluate the effectiveness and efficiency of the proposed method